2020
DOI: 10.3390/cells9061495
|View full text |Cite
|
Sign up to set email alerts
|

Update on Circulating Tumor Cells in Genitourinary Tumors with Focus on Prostate Cancer

Abstract: Current developments in the treatment of genitourinary tumors underline the unmet clinical need for biomarkers to improve decision-making in a challenging clinical setting. The detection of circulating tumor cells (CTCs) has become one of the most exciting and important new approaches to identifying biomarkers at different stages of disease in a non-invasive way. Potential applications of CTCs include monitoring treatment efficacy and early detection of progression, selecting tailored therapies, as well as sav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…Circulating cell-free DNA (cfDNA) in blood acquired from plasma using a simple blood test provides repeated serial access to tumor DNA as a minimally invasive “liquid biopsy.” Liquid biopsy includes cell-free nucleic acid, circulating tumor cells, extracellular vesicles, metabolites, and proteins [ 20 , 21 , 22 ].…”
Section: Biology Of Ctdnamentioning
confidence: 99%
“…Circulating cell-free DNA (cfDNA) in blood acquired from plasma using a simple blood test provides repeated serial access to tumor DNA as a minimally invasive “liquid biopsy.” Liquid biopsy includes cell-free nucleic acid, circulating tumor cells, extracellular vesicles, metabolites, and proteins [ 20 , 21 , 22 ].…”
Section: Biology Of Ctdnamentioning
confidence: 99%
“…Based on these scientific findings, a wide variety of clinical studies were carried out. Reports in the literature, for example, have demonstrated that cancer patients with a higher number of CTCs normally have a poorer prognosis than those with a lower number of CTCs [ 8 , 9 , 10 ]. Moreover, the predictive roles of CTCs for specific cancer therapies have also been demonstrated in different scenarios in patients with breast [ 11 ], head and neck [ 12 ], or prostate cancers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports in the literature, for example, have demonstrated that cancer patients with a higher number of CTCs normally have a poorer prognosis than those with a lower number of CTCs [ 8 , 9 , 10 ]. Moreover, the predictive roles of CTCs for specific cancer therapies have also been demonstrated in different scenarios in patients with breast [ 11 ], head and neck [ 12 ], or prostate cancers [ 9 ]. The prognostic role of CTCs has also been proven for patients with CRC after or during anticancer therapy [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide range of novelties reported in this Special Issue of the journal Cells on prostate cancer (PCa) diagnosis, prognosis, and prediction to response to therapy, has led us to a series of considerations related to a better understanding of the current and future role of effective molecular biomarkers in individual patients with PCa [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]: (1) Digital pathology, including multiplexing; (2) Clinical translation of genetic information; (3) Clinical significance of liquid biopsies; and (4) Multi-criteria decision making and information fusion.…”
mentioning
confidence: 99%